The Impact of Endometriosis on Mental Health - A Literature Review of Depression and Anxiety Symptoms - Woźniak, Julia; Kadłubek, Sabina; Mąka, Magdalena; Kapturska, Natalia; Kalinowski, Szymon; Cymerys, Kinga; Kardaszewski, Piotr; Kamiński, Jakub; Sikora, Dominik; Góralczyk, Ewa (Journal of Education, Health and Sport, 2025)
Introduction and purpose: Endometriosis is a gynecological disease that affects about 10% of women worldwide. Women suffering from endometriosis are susceptible to mental health disorders, such as depression and anxiety. It is essential to highlight the psychological struggles of women with endometriosis in order to integrate physical and psychological care and subsequently enhance the treatment outcomes. Materials and Methods: Medical databases such as Pubmed, Embase, Google Scholar were searched for scientific papers on endometriosis and its relationship with the symptoms of depression and anxiety. Research outlined the influence of endometriosis treatment, social stigmatization and non-medicinal approach. State of knowledge: The prevalence of depression and anxiety among women with endometriosis is significant. The symptoms of the disease influence daily struggles, relationship with partners and family, education and career responsibilities, subsequently lowering the quality of life. Women with endometriosis experience social stigmatization manifested not only from society members but also from healthcare professionals. The approach to the medical treatment by patients was discovered to be of consequence. Literature review emphasizes the benefits of psychological support and empathetic attitude of medical practitioners. Conclusions: Multidisciplinary team is essential in order to provide intervention strategies leading to greater therapeutic outcomes in endometriosis treatment. Endometriosis and mental disorders are inextricably connected. More research is needed to accent the importance of mental health in the treatment of physical conditions.